Effect of ultrahigh frequency ozone therapy on oxidative metabolism in the blood of rats with ischemic skin flaps: A preclinical experimental randomized study - A. K. Martusevich; I. E. Sazonova; A. G. Soloveva; N. Yu. Orlinskaya; V. V. Kononets; L. R. Dilenyan (Кубанский научный медицинский вестник, 2024)
Background. Maintaining and restoring skin microcirculation in surgical flaps, as well as accelerating rehabilitation after skin flap transplantation, in order to mitigate the consequences of burns and injuries, remain a pressing issue. In addition to various timings and techniques for plastic surgery, physiotherapeutic approaches prove to be efficient and include low-intensity electromagnetic radiation in millimeter waves as their prominent techniques. In recent years, experts have paid an increasing attention to the application of low-intensity electromagnetic radiation across different frequency ranges for the enhancement of microcirculation in patients after surgical correction of burn consequences. However, this approach is yet to be further validated. Objective. To investigate the effect of different combinations of ultrahigh frequency electromagnetic radiation with ozone therapy on the oxidative metabolism of blood in rats using a model of ischemic skin flaps. Methods. A preclinical experimental randomized study was conducted on 100 adult male Wistar rats weighing between 200 and 250 grams. Five equal-sized groups of animals were formed in the study: Group 1: intact (no interventions), and Groups 2, 3, 4, and 5: after surgical intervention (modeling of ischemic skin flaps). Animals in Group 2 (control group) received no therapeutic procedures. Rats in Groups 3 and 5 underwent a 10-minute course of electromagnetic radiation exposure with a dose of 0.06 mJ for seven days. Animals in Group 3 were exposed to electromagnetic radiation of ultrahigh frequency with a range of 53–78 GHz. Animals in Group 4 received injections of ozonized saline solution (with a saturating ozone concentration in the ozonized oxygen mixture of 3000 µg/L) daily for 7 days, administered intraperitoneally at a volume of 1 mL. Group 5 underwent a combined treatment: daily exposure to ultrahigh frequency electromagnetic radiation along with intraperitoneal ozone therapy (the application modalities of these treatments were similar to those used in Groups 3 and 4, respectively). The intensity of lipid peroxidation, peroxide resistance in erythrocytes, and overall antioxidant system activity were assessed in order to investigate the balance of pro- and antioxidant systems in plasma and erythrocytes. Additionally, the study involved determination of the level of malondialdehyde content and evaluation of the activity of superoxide dismutase and catalase in erythrocytes. The obtained date were analyzed, using MS Office 2013 (Microsoft Corporation, USA) and Statistica 10 (StatSoft, USA). Results. The conducted analysis revealed an antioxidant effect from ultrahigh frequency electromagnetic radiation, with this effect being enhanced by ozone therapy. In addition, the study detected the inhibition of free radical oxidation under the ultrahigh frequency electromagnetic radiation and ozone therapy. Conclusion. Thus, the positive effects of the studied therapeutic factors manifest at the systemic level, as evidenced by the optimization of biochemical parameters and indicators of oxidative metabolism in the plasma of animal blood. It has been established that ultrahigh frequency electromagnetic radiation, administered in a noise mode, exerts a regulatory effect on pro- and antioxidant systems in the body, as demonstrated in a model of transplanted skin flap. This intervention leads to a reduction in the severity of oxidative stress and an enhancement of antioxidant reserves in the blood. The observed effect is further amplified with the additional application of ozone therapy.